A theory of mindfulness caring in community health nursing - Suwarsi, Suwarsi; Baua, Elizabeth C. (International Journal Of Community Medicine And Public Health, 2021)
Most adolescent mortality and morbidity is preventable or treatable, but adolescents face specific barriers in accessing health information and services. The problems in the community in the youth group are free sex behaviour, the use of alcohol and drugs. This research to develop a caring theory model that can be applied by community nurses in the community in enhancing the awareness of adolescent age groups in the community. Research method used conceptual paper are based on previous research that the author has done (4 articles) and combines the literature review (7 results) that the author has done from April-November 2020. Result in this research indicate that the theory will become the bases or foundation for nurses to become mindful of their role as community health nurses. They need to optimize their Role in Caring for community adolescents in addressing societal problems like drug abuse, teenage pregnancy. Public awareness involves collaboration between governments by making people aware of existing laws and policies. National strategies and action plans for adolescent-specific health policies; Health management: health human resources, health facilities, networks: community health cadres, school communities; Family and peers are needed to increase awareness of adolescent behaviour so that through caring a sense of empathy and youth will be realized. Conclution in this research is nurses can apply the theory of mindfulness caring. Problems related to adolescent behavior can be overcome with cooperation in various sectors, so awareness by these sectors is the key in preventing the impact of deviant adolescent behavior.